2016
DOI: 10.1177/00333549161310s104
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Implementing a Routine HIV Screening Program in Two Federally Qualified Health Centers in the Southern United States

Abstract: Southside and Central Care effectively implemented routine HIV screening programs that dramatically increased their testing volume while also linking the majority of HIV-positive patients to care. Other community health centers should consider similar programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…look-alike health centers (community-based health centers that meet the requirements of the HRSA Health Center Program, but do not receive Health Center Program funding § § ) since 2014. ¶ ¶ Some CHCs have also implemented clinical decision support algorithms for increasing HIV testing (5,6). HIV testing did not increase in physician offices during 2014-2016, despite elimination of patient cost-sharing, possibly because testing barriers unrelated to cost have not been addressed (e.g., dependence on busy providers to order HIV tests).…”
Section: Discussionmentioning
confidence: 99%
“…look-alike health centers (community-based health centers that meet the requirements of the HRSA Health Center Program, but do not receive Health Center Program funding § § ) since 2014. ¶ ¶ Some CHCs have also implemented clinical decision support algorithms for increasing HIV testing (5,6). HIV testing did not increase in physician offices during 2014-2016, despite elimination of patient cost-sharing, possibly because testing barriers unrelated to cost have not been addressed (e.g., dependence on busy providers to order HIV tests).…”
Section: Discussionmentioning
confidence: 99%
“…Most impressively, our linkage to care rates of 64% (HCV) and 100% (HIV) are among some of the highest reported, which has typically been shown to vary between 30-40% for HCV and 60-80% for HIV seropositive patients, respectively. [16,17,19] Our rates may be higher than prior studies for a number of reasons. First, PNs were able to contact patients via texting per patient preference, and texting as a means of contacting patients-particularly younger patients-has been suggested as a successful strategy for hard-to-reach patients such as PWID and is novel to our FOCUS study.…”
Section: Resultsmentioning
confidence: 56%
“…[13] Previous studies have successfully used the EMR to increase screening for HIV and other infectious diseases. [14][15][16][17][18][19] However, all were conducted in urban areas not currently in the midst of a burgeoning opioid epidemic like the current one affecting central Appalachia.…”
Section: Importancementioning
confidence: 99%
“…The objectives of routine screening are to increase the proportion of HIV-infected individuals who are aware of their infection, facilitate early HIV diagnosis, provide timely linkage to care, and normalize screening to reduce stigma associated with HIV testing. Several studies have shown that offering routine screening is, indeed, associated with an increased uptake of testing, especially when testing is recommended by a healthcare provider [28].…”
Section: Introductionmentioning
confidence: 99%
“…Among these individuals, 75% reported not being offered an HIV test during any of their healthcare visits [14]. Such findings may be attributed to a lack of provider awareness about HIV testing guidelines and failure to implement operational procedures for routine testing [2, 1516]. A 2014 review of HIV testing barriers found that only 2.0–35.8% of providers offer routine HIV testing while most continue to perform risk-based testing [15].…”
Section: Introductionmentioning
confidence: 99%